Integrating Inquiry-Based Learning with PHET Simulations: A Strategy to Enhance Higher-Order Thinking Skills - Nasar, Adrianus; Sinar, Yunitasia; Nanut, Fransiska Alvi (Universitas Muhammadiyah Makassar, 2025)
Enhancing Higher-Order Thinking Skills (HOTS) is essential in physics education to prepare students for analyzing and solving real-world problems. However, in under-resourced regions such as Flores, Indonesia, the development of HOTS is hindered by limited access to laboratories and traditional teacher-centered approaches. This study investigates the effectiveness of integrating Inquiry-Based Learning (IBL) with PhET simulations as an instructional strategy to improve HOTS among university students. Using a one-group pretest-posttest experimental design, the study involved 36 students from the Physics Education Program at Universitas Flores. Students were exposed to four simulation-based inquiry sessions on alternating current (AC) circuits. HOTS were assessed through a 15-item test targeting analysis, evaluation, and creation dimensions, with data analyzed using a paired-sample t-test. The results revealed a significant improvement in students’ HOTS, as indicated by the increase in average scores from 70.67 to 79.64 (p 0.001), with the most notable gain observed in the 'Create' category. The integration of IBL with PhET provided an interactive, contextual, and student-centered learning experience that supported conceptual understanding and cognitive engagement. Despite challenges related to infrastructure and teacher readiness, the findings highlight the potential of this approach in promoting critical and creative thinking. This study contributes to physics education by offering a scalable and cost-effective instructional model that aligns with 21st-century learning demands, particularly in resource-constrained environments.